Analysis of the chain value of wild edible mushrooms in the mountain area of the province of Chubut, Patagonia, Argentina - Fernández, María Victoria; Pildaín, María Belén; Barroetaveña, Carolina (BOSQUE, 2025)
Edible mushrooms have gained special interest in recent decades because of their value as functional foods and potential for the development of local economies. In the forested area of Chubut mountain range, various species of edible wild mushrooms proliferate, indicating the economic value of Morchella spp. and Suillus luteus. Through a survey of products, a structured survey and open interviews aimed at different actors, this study analyzed, in the tourist towns Esquel and Trevelin, the chain value of the collected species and the presence in stores of these and others cultivated such as Pleurotus spp., Lentinula edodes and Agaricus bisporus, The results showed that 76.3 % of the businesses surveyed offer products related to edible mushrooms, mainly S. luteus with local added value and competition from products made in other regions. In the case of Morchella spp., a lower local added value and a consumption and secondary processing market developed in Europe were observed. The other species had a lower presence and diversity of products, with the exception of Agaricus bisporus, which was not produced in the region. The beginning of the chain is an informal activity carried out regularly by many collectors, which concentrates on a few actors towards the end. Consumption is not completely natural. The findings indicate that there are opportunities to diversify the production of the local agri-food market, assuming a sustainable collection scheme accompanied by policies to expand demand and support for intermediate and initial actors in the chain.